The subjective well-being in Peruvian adolescence: Identifying domains and evaluations in a non-WEIRD context - (:unkn) unknown (John Wiley & Sons, Inc., 2024)
The present qualitative study examined how a group of Peruvian adolescents (N = 32) from different cultural contexts conceive their well-being. The goal was to identify the domains that structure their conception of well-being and how they evaluate i...
Keywords: Bienestar subjetivo; Adolescencia